Formulasi Pengaturan Intersepsi Dalam Pemberantasan Korupsi Di Era Digital Oleh Kejaksaan Republik Indonesia - Rudi Dwi Prastyono (Universitas Islam Indonesia, 2020)
This study aims to construct legal reform in the disclosure of cases of corruption which tend to be massive and hidden. This study aims to reach the formulation of regulation of corruption case disclosure in the digital era in the form of a strategy to eradicate corruption by using the interception method by the Prosecutor's Office in accordance with the laws and regulations after the Constitutional Court decision Number 5/PUU-VIII/2010. This research uses normative methods through laws and regulations, books and documents. The results of the study conclude, first, that the interception authority in the digital era by prosecutors as investigators, investigators, public prosecutors and executors in eradicating corruption has not received legal legitimacy, so that with the broad authority of the Attorney General's Office and the structure that has been spread throughout Indonesia, it is now necessary supported by the interception authority. Second, the formulation of interception regulation for prosecutors in the future needs to be regulated in a statutory level, and regulated in detail in order to accommodate and limit the authority of law enforcement officials, especially prosecutors in conducting interception.